Aesthetic assessment of maxillary lateral and canine implant-supported crowns by laypersons and orthodontists - Nina Sabel; Erika Toft; Erica Johansson; Julia Naoumova (Medical Journals Sweden, 2024)
Introduction: The objectives of this study were to evaluate how laypersons and orthodontists evaluate and rank aesthetic parameters of an implant-supported crown (ISC) on the canine position (ISC-C) and lateral position (ISC-L). Methods: A digital survey of 11 cases, 5 ISC-C, 5 ISC-L and 1 control case without ISC, was distributed to 207 laypersons and 296 orthodontists. All cases included one extraoral photograph and three intraoral photographs. The respondents were asked to identify the ISC and to evaluate the aesthetic parameters regarding colour of the implant (CI), shape of the implant (SI) and gingival colour around ISC (GCI). Differences within and between the groups were tested using Chi-2-test and Independent-Samples t-test. Results: All invited laypersons and 184 orthodontists (62% response rate) answered the survey. Orthodontists (89%) more correctly identified the ISC, regardless of its position, than laypersons (50%) (p < 0.001). Both laypersons (54%) and orthodontists (23%) rated higher proportions of acceptance of CI, SI and GCI in favour for the ISC-L than ISC-C (laypersons: 40%, orthodontists: 10%) (p < 0.001). Assessing each parameter separately, orthodontists rated higher for ISC-L, compared to the ISC-C (p < 0.001). In general, laypersons and orthodontist ranked tooth colour (mean, standard deviation [SD]:8.0,1.5 and 9.0, 1.0) and tooth shape (mean, SD: 8.0, 1.7 and 8.8, 1.2) as aesthetically higher than the gingival colour (mean, SD: 7.2, 2.2 and 8.0, 1.7) (p > 0.001).  Conclusion: Laypersons and orthodontists consider the ISC-L as aesthetically more preferable, compared to the ISC-C.